2012
DOI: 10.1332/204674312x656301
|View full text |Cite
|
Sign up to set email alerts
|

Blinded by neuroscience: social policy, the family and the infant brain

Abstract: Current social policy initiatives are promoting early intervention to improve the lives of disadvantaged children. Neuroscientific evidence is prominent in this discourse, creating the lustre of science, but too much has been taken on trust. In particular, the argument that the first three years are critical has created a now-or-never imperative to intervene before irreparable damage is done to the developing infant brain. A critique of current policy in the United Kingdom is provided here, drawing on counter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 20 publications
1
128
0
2
Order By: Relevance
“…By examining our respondents' discussions of "scientific research" (which we understand here both as actual specific scientific articles and findings, and an imagined and assumed neurobiological "canon"), we adopt a "symmetrical" position common in the sociology of scientific knowledge (SSK) (Bloor 1991) and other traditions within STS. Accordingly, we diverge from the interests of some other authors concerned with neuroscience and policy (for example, Macvarish, Lee, and Lowe 2014;Wastell and White 2012;Edwards, Gillies, and Horsley 2015). Our principal concerns lie neither with the accuracy of our respondents' understandings of neuroscience, nor the appropriateness of the uses to which it is put.…”
Section: Neuroscience In Policy and Practicementioning
confidence: 87%
See 1 more Smart Citation
“…By examining our respondents' discussions of "scientific research" (which we understand here both as actual specific scientific articles and findings, and an imagined and assumed neurobiological "canon"), we adopt a "symmetrical" position common in the sociology of scientific knowledge (SSK) (Bloor 1991) and other traditions within STS. Accordingly, we diverge from the interests of some other authors concerned with neuroscience and policy (for example, Macvarish, Lee, and Lowe 2014;Wastell and White 2012;Edwards, Gillies, and Horsley 2015). Our principal concerns lie neither with the accuracy of our respondents' understandings of neuroscience, nor the appropriateness of the uses to which it is put.…”
Section: Neuroscience In Policy and Practicementioning
confidence: 87%
“…The visibility of the neurosciences within UK policy has been documented extensively in recent years (Broer and Pickersgill 2015;Macvarish, Lee, and Lowe 2014;Wastell and White 2012;Edwards, Gillies, and Horsley 2015). A feature of much of this literature is a critique of policymakers, who are often regarded as misusing the neurosciences (Wastell and White 2012, 402;Edwards, Gillies, and Horsley 2015;Lowe, Lee, and Macvarish 2015a;Lowe, Lee, and Macvarish 2015b.)…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ECEC, the result has been a privileging of a particular view of learning and knowledge. Within these global policy objectives there is evidence of infant determinism, whereby there are enlightenment goals that can be reached (Wastell & White, 2012). The dominance of human capital theory in policy developments privileges cognitive development and the acquisition of knowledge, despite the evidence that ECEC is just as important (if not more so) for social development.…”
Section: Discussionmentioning
confidence: 99%
“…In England, the Effective Provision of Pre-school Education (EPPE) research has been particularly influential in demonstrating the importance of early education, particularly for children from disadvantaged backgrounds (Sylva et al, 2004). However, more recent evidence has suggested that the impacts identified in the early US studies, such as Head Start, are transient (Wastell & White, 2012), whilst other research has found that the impact of ECEC in England, whilst being present, are not significant (Hopkins et al, 2010). There are obviously questions surrounding the outcomes that have been assessed, with concern being raised that there has been a preoccupation with cognitive developments at the expense of social outcomes, but also that it is hard to pin point what has had any kind of influence on child development (Wastell & White, 2012).…”
Section: Human Capital Theory and Ececmentioning
confidence: 98%
“…It is critiqued heavily in social science and neuroscience (Rose and Rose 2016;Featherstone et al 2013, p. 5). Wastell and White (2012) find no good quality scientific evidence behind it, suggesting that the images are used for shock value. The UK followed the US' example in which neuroscience 'was chosen as the scientific vehicle for the public relations campaign to promote early childhood programmes more for rhetorical, than scientific reasons' (Bruer 2011, p. 2;1999;see also Gillies 2014).…”
Section: Uk Government 'Troubled Families' Policy: Examples Of Egregimentioning
confidence: 99%